Analisis Sistem Pengendalian Manajemen di LAZISNU Ranting Klampok di Desa Klampok Kecamatan Benjeng Kabupaten Gresik - Issatun Adillia Rasyid Sasa; Airlangga Bramayudha (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2023)
The digital era has led us to participate in the flow of pucliv conversation that is not certain. A lot of content is produced, but we cannot confirm the truth of the content. In addition, the existence of a religious moderation framework must be implemented, especially on media social. AIS Nusantara as a community of sudent who concentrate in the digital space takes this role in implementing religious moderation in the digital spacae. This study uses netnographic reseacrh, namely planning reseaerch implementation, compiling problem formulation and study object from sosial media, data collection, data interpretation which includes data classification and coding. AIS Nusantara has a strategic role to easetensions and clear up various discourses and issues that are carried freely in the digital space with the existence of the AIS Nusantara community with many accounts that have milions of followers able to construct discourses on sosial media.